Features of the Organization of Industrial Production on the Basis of Orders - Nasimdjan, Babaev (European Journal of Life Safety and Stability (2660-9630), 2021)
This article provides practical suggestions and recommendations on how to properly organize the order portfolio in the activities of enterprises, timely and quality execution of orders. In addition, timely execution of orders will increase the number of customers of the company.